AB0704 Red blood cell but not plasma phospholipids profile may be associated with the presence of carotid plaques in women with systemic lupus erythematosus. (23rd January 2014) - Fortin, P.R.; Aghdassi, E.; Ma, D.W.; Eder, L.; Morrison, S.; Frattasi, M.; Su, J.; Gladman, D.D.; Lonn, E.L.; Harvey, P.
Abstract : Background: Alterations in Phosphatidylcholine (PC) to Phosphatidylethanolamine (PE) ratio (PC:PE) have been associated with adverse outcomes in patients with chronic inflammatory conditions. Auto-antibodies to PC and PE are reported in patients with systemic lupus erythematosus (SLE) and this may lead to changes in blood and cell membranes PC, PE and PC:PE. Objectives: The objective of this study was to determine whether red blood cell (RBC) and/or plasma levels of PC, PE or PC:PE were altered in women with SLE and carotid plaques (CP) on ultrasound (US) when compared to those without plaques. Methods: Women with SLE attending an academic centre were enrolled consecutively. They underwent a vascular US in which the carotid intimal medial thickness (CIMT) and the presence of CP were estimated. Phospholipids profile was determined in RBC and plasma using thin layer and gas chromatography. Demographic variables, cardiovascular disease (CVD) risk factors and SLE disease activity (SLEDAI-2K) and damage (SLICC/ACR damage index or SDI), fasting blood lipid profile, glucose and insulin were collected. CIMT and RBC and plasma PC, PE and PC:PE were compared between patients with and without CP using un-paired student t-test. Multivariate logistic regressions using presence of CP as outcome variable, PC, PE or PC:PE as predictor variable and adjusted for age and hypertension were performed. Results: To date 114 of the 208 women enrolled underwent assessment. Forty (35.1%) had CP and 92 (36 with and 56 without CP) had data available on their RBC and plasma phospholipids profile. Among the CVD risk factors, only age [58.1 (12.3) vs. 44.1 (9.6) year, p=0.001] and systolic blood pressure [130.0 (18.1) vs. 118.6. (15.1) mmHg; p=0.002] were significantly higher in SLE women with CP compared to those without. Blood total cholesterol, LDL and HDL cholesterol, glucose and insulin as well as body mass index, smoking prevalence and waist to hip ratio were all similar between the two groups. CIMT was significantly higher [674 (116) vs. 583 (76) mm, p=0.001] and the RBC PC [28.8 (5.0) vs. 31.7 (5.9), p=0.017] was significantly lower in women with the carotid plaques compared to those without. There were no differences in the RBC PC:PE [1.27 (0.21) vs.1.33 (0.29), p=0.288], plasma PC [54.2 (22.2) vs. 52.5 (15.6), p=0.71] or plasma PC:PE [19.5 (7.4) vs. 18.9 (4.7), p=0.69] between the two groups. The multivariate analysis showed that age [OR=1.093, (95%CI=1.038, 1.150)] and systolic blood pressure [1.038 (1.001, 1.031)] remained significant while RBC PC was no longer significant [0.937 (0.852, 1.031)]. Conclusions: RBC, but not plasma, PC level was significantly lower in those with carotid plaques in univariate analysis. Age and systolic blood pressure were the only significant variables in the multivariate analysis while PC was no longer significantly associated with plaques. Disclosure of Interest: P. Fortin Consultant for: GSK, Roche, Speakers Bureau: GSK, Actelion, E. Aghdassi: None Declared, D. Ma: None Declared, L. Eder: None Declared, S. Morrison: None Declared, M. Frattasi: None Declared, J. Su: None Declared, D. Gladman: None Declared, E. Lonn: None Declared, P. Harvey: None Declared